Relation of recurrent miscarriages with some of fertility hormones - Dr. Rehab Jasim Mohammed; Asst.Lect. Aseel Ehsan Mahmoud (Zien Journals, 2023)
The loss of a pregnancy before the fetus is viable is referred to as a miscarriage. Depending on the data source, this might be considered as being 20 or 24 weeks pregnant. Threatened miscarriage occurs during the first 20 weeks of pregnancy, with pain or without pain. A miscarriage occurs in 10% to 15% of all clinically confirmed pregnancies. Recurrent miscarriages, typically defined as three or more spontaneous miscarriages, affect 1% to 2% of couples. There may never be a cure for recurrent miscarriage for many women and their partners. Pregnancies may now be identified sooner, even if they are going to end in an early miscarriage, thanks to advancements in pregnancy testing and ultrasound technology. These may not have been noticed in the past. Consequently, more women may report losing an early pregnancy. Both couples may experience severe emotional grief if a miscarriage occurs. Initial emotional numbness and denial, anxiety, shock, grief, emptiness, rage, inadequacy, blame, and envy, melancholy, sleep trouble, social isolation, hostility, and marital conflict have all been documented as emotional responses to pregnancy losses
Keywords: Recurrent miscarriages; Fertility hormones